2019
DOI: 10.1186/s13046-019-1429-z
|View full text |Cite
|
Sign up to set email alerts
|

NANOG helps cancer cells escape NK cell attack by downregulating ICAM1 during tumorigenesis

Abstract: Background At the beginning of tumorigenesis, newly born cancer cells must successfully avoid attack by the immune system. Although most abnormal cells are efficiently identified and destroyed by the immune system, particularly by NK cells, the molecular mechanisms by which newly born cancer cells evade NK cell surveillance are not fully understood. Methods NK cell resistance of highly tumorigenic population of human prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Compared to nontreated cells, the expressions of cell adhesion molecules and ECM (extracellular matrix)-receptor interaction molecules were significantly downregulated in EPS364-treated cells ( Figure 6 A). The expressions of cell adhesion molecules, especially ALCAM (activated leukocyte cell adhesion molecule) and ICAM1 (intercellular adhesion molecule 1), which have been reported to play vital roles in cancer cell adhesion [ 26 , 27 , 28 , 29 ], were remarkably downregulated ( Figure 6 B). Downregulating the expression of adhesion molecules indicated that the cell adhesion capability was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to nontreated cells, the expressions of cell adhesion molecules and ECM (extracellular matrix)-receptor interaction molecules were significantly downregulated in EPS364-treated cells ( Figure 6 A). The expressions of cell adhesion molecules, especially ALCAM (activated leukocyte cell adhesion molecule) and ICAM1 (intercellular adhesion molecule 1), which have been reported to play vital roles in cancer cell adhesion [ 26 , 27 , 28 , 29 ], were remarkably downregulated ( Figure 6 B). Downregulating the expression of adhesion molecules indicated that the cell adhesion capability was reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, tumor cells (not just PCa cells) express several surface markers or immunocyte regulatory factors to escape NK cells. With PCa cells, the stem cell marker, nanoG, was proven to help PCa cells to escape destruction by NK cells through downregulating intercellular adhesion molecule 1 (iCAMP1) [59]. Additionally, nanoG also triggers various cancer stem cell markers and chemokine receptors, such as C-X-C motif receptor 4 (CXCR4), CD133, aldehyde dehydrogenase 1 (ALDH1), and insulin-like growth factor (IGF)-binding protein 1 (IGFBP1) [60].…”
Section: Surface Modulation Of Pca During Circulationmentioning
confidence: 99%
“…Next, we examined if the shape of the end of the DNA coding the selection marker was critical for generating KO clones using high blasticidin S concentration. Although introduction of an un-cut plasmid with a selection marker is known to establish transgenic clones by random integration of the plasmid into the genome 11 , the un-cut plasmid with a selection marker did not allow cells to form colonies under the high antibiotic dose (Fig. 3 A).…”
Section: Resultsmentioning
confidence: 99%